Giant Hepatic Hemolymphangioma With Peritoneal Effusion in Children: A Case Report and Literature Review - Li, Yufeng; Ta, Lei; Xu, Yuan; Liu, Jianli (Frontiers in Pediatrics, 2022)
Hemolymphangioma is a congenital malformation of blood vessels and lymphatic vessels, commonly found in the head, neck, and subcutaneous, rare in the viscera, and extremely rare in the liver. In this case, a 6-year-old boy was found to have abdominal distension for more than 2 months with no other obvious symptoms. Physical examination revealed a large abdominal mass that was hard and not mobile. Laboratory tests found no obvious abnormity. Preoperative ultrasound and CT showed a huge cystic and solid-cystic tumor in the abdomen with close relationship to the right lower margin of the liver and fluid accumulation in the abdominopelvic cavity. The preliminary diagnosis was malignant tumor of embryonic origin and undifferentiated sarcoma. Liver tumor resection was performed in our hospital, and the postoperative pathology was diagnosed hepatic hemolymphangioma. The patient recovered well after surgery. A large abdominal mass in the child is easy to be diagnosed as a malignant tumor of the liver and delay the treatment; no obvious symptoms, no obvious abnormalities in laboratory tests, and imaging shows a multiocular cystic lesion with clear borders and no invasion of blood vessels, indicating that the possibility of this disease should be considered; the tumor has an abnormal rich blood supply, and preoperative imaging evaluation clearly shows the vascular pathway and blood supply status to help optimize the surgical plan.